A metallic Cu2N monolayer with planar tetracoordinated nitrogen as a promising catalyst for CO2 electroreduction. Issue 3 (4th January 2022) - Jia, Jingjing; Wang, Zhongxu; Liu, Yu; Li, Fengyu; Shang, Yongchen; Liu, Yuejie; Cai, Qinghai; Zhao, Jingxiang
Abstract : By means of a particle swarm optimization search and density functional theory computations, we predicted a hitherto unknown Cu2 N monolayer with planar hexacoordinate Cu and tetracoordinate N atoms as a CO2 RR catalyst. Abstract : The electrochemical carbon dioxide reduction reaction (CO2 RR) holds great promise for mitigating CO2 emission and simultaneously generating high energy fuel. However, it remains a great challenge to reduce CO2 to C2 products due to the lack of highly efficient catalysts. Herein, by means of a particle swarm optimization search and comprehensive density functional theory (DFT) computations, we predicted a hitherto unknown Cu2 N monolayer with planar hexacoordinate Cu and tetracoordinate N atoms as a CO2 RR catalyst. Our results revealed that the Cu2 N monolayer shows outstanding stability and intrinsic metallicity. Interestingly, the as-designed Cu2 N monolayer exhibits superior CO2 RR catalytic performance with a rather low limiting potential (−0.33 V), resulting in the formation of a C2 H4 product with a small kinetic barrier (0.55 eV) for the coupling between *CH2 and a CO molecule. Strikingly, the N atoms within the Cu2 N monolayer were revealed to be the CO2 RR active sites due to their significant binding strength with the CO2 RR species and their significant spin moments. Our findings not only propose a useful roadmap for the discovery of 2D hypercoordinate materials, but also provide cost-effective opportunities for advancing sustainable CO2 conversion.